Quick of Blood Sebagai Salah Satu Faktor yang Mempengaruhi Tercapainya Adekuasi Hemodialisa - Wayunah, Wayunah; Prabowo , Ridho Kunto; Fatimah , Imah; Saefulloh , Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Introduction. Hemodialysis therapy is a kidney replacement therapy that functions to remove metabolic waste resulting from kidney damage. The hemodialysis dose is adjusted to the patient's needs. One of the factors that influence the achievement of adequacy is quick blood flow (Qb). The higher the Qb, the more adequacy will be achieved, but it is not yet known how much Qb speed influences the achievement of hemodialysis adequacy. This research aims to determine the relationship between quick blood flow and hemodialysis adequacy. Method. This research uses descriptive analytical methods with a cross-sectional approach. The population in this study was 133 patients undergoing hemodialysis at the Indramayu District Hospital and a sample of 44 respondents using a purposive sampling technique. This research instrument uses an observation sheet and data is analyzed using the chi-square test. Result. The average quick of blood for patients was 270.57 ml/minute. A total of 24 (54.5%) respondents had Qb ? 270.57 ml/minute and 24 (54.5%) respondents achieved adequacy. The results of further analysis obtained a p-value of 0.029 (? < 0.05), meaning that there was a relationship between quick blood flow and hemodialysis adequacy in chronic kidney failure patients in the Hemodialysis Room at Indramayu District Hospital. Conclusion. Quick of blood is related to hemodialysis adequacy. Suggestions are aimed at nurses to adjust Qb according to the patient's dose, namely a minimum of 270 ml/minute so that adequacy is achieved.